Molecular Characterization of Endosulfan Tolerant Rhizospheric Microbes from Tea Gardens of Silchar Assam, India - Qazi Mohd Rizwanul Haq2, Gauri Dutta Sharma1*, Pratibha Huidrom1,a, Arif Tasleem Jan2, (Journal of Experimental Sciences, 2011)
<div style="border-right: medium none; padding-right: 0in; border-top: windowtext 1pt solid; padding-left: 0in; background: white; padding-bottom: 0in; border-left: medium none; padding-top: 1pt; border-bottom: medium none; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> 16s rDNA gene analysis is one of the most reliable techniques for identification of unknown and uncultured bacterial strains as sequence of rRNA molecule is highly conserved between organisms. Following growth on selective media, identification of the endosulfan metabolizing rhizospheric microbes inhabiting roots of shade trees (Albizia sp.) from selected tea garden soils of South Assam, was done by performing PCR amplification of 16S rRNA gene followed by cloning in to pGEMT® easy vector. Molecular identification and phylogenetic analysis of 16S rRNA gene sequences revealed that tea garden soils harbored bacterial species belonging to Rhizobium, Burkholderia and Enterobacter. Identification of bacterial strains growing under heavy input of chemicals in the form of fertilizers and pesticides from tea garden soils, have spurred continued interest in exploring prokaryotic diversity and its relationship to ecosystem processes that can be exploited for developing effective bioremediation strategies so as to remediate pollutants from the environment.